Using Action Research to tackle constraints to collaborative university work: a case of Widening Participation - Webster-Deakin, Tara DL (2022)
This thesis focuses on my work as a professional member of staff in one academic School in a higher-status UK university (Midtown). Specifically, it explores the process of tackling the constraints to collaboration between professional university and academic staff through the medium of action research and using the case and location of my work, widening participation (WP). The research was motivated by my desire to understand why academics often appeared reluctant to engage with WP work, and by my interest in action research as a mutually supportive approach to delivering the WP agenda. The research, therefore, was informed by action research principles of collaboration, co-construction of knowledge and action for social change and involved me, and three academics.